Longitudinal contributions of morphological awareness, listening comprehension, and gains in word reading fluency to later word- and text-reading fluency - Metsala, Jamie L. (Frontiers in Education, 2023)
This study examined the contributions of morphological awareness, listening comprehension, and early gains in word reading fluency to later outcomes in word- and text- reading fluency. There were 83 participants in second and third grade at study onset, who were followed across 18 months. Gains in word reading fluency across the first six months predicted both word- and text-reading fluency one year later, beyond variance accounted for by initial word reading fluency, phonological awareness, rapid naming, and two oral language skills. Initial morphological awareness predicted reliable additional variance in word- and text-reading fluency 18 months later. The contribution of listening comprehension was specific to outcomes in text reading fluency. In the last analyses, listening comprehension, but not morphological awareness, predicted unique variance in final text reading fluency beyond final word reading fluency. Findings are discussed in terms of the developmental time-course of reading fluency and the roles of the two oral language skills examined.